Prognostic Biomarker DDOST and Its Correlation With Immune Infiltrates in Hepatocellular Carcinoma - Zhu, Changyu; Xiao, Hua; Jiang, Xiaolei; Tong, Rongsheng; Guan, Jianmei (Frontiers in Genetics, 2022)
Background: Dolichyl-diphosphooligosaccharide–protein glycosyltransferase non-catalytic subunit (DDOST) is an important enzyme in the process of high-mannose oligosaccharide transferring in cells. Increasing DDOST expression is associated with impairing liver function and the increase of hepatic fibrosis degrees, hence exacerbating the liver injury. However, the relation between DDOST and hepatocellular carcinoma (HCC) has not been revealed yet. Method: In this study, we evaluated the prognostic value of DDOST in HCC based on data from The Cancer Genome Atlas (TCGA) database. The relationship between DDOST expression and clinical-pathologic features was evaluated by logistic regression, the Wilcoxon signed-rank test, and Kruskal–Wallis test. Prognosis-related factors of HCC including DDOST were evaluated by univariate and multivariate Cox regression and the Kaplan–Meier method. DDOST-related key pathways were identified by gene set enrichment analysis (GSEA). The correlations between DDOST and cancer immune infiltrates were investigated by the single-sample gene set enrichment analysis (ssGSEA) of TCGA data. Results: High DDOST expression was associated with poorer overall survival and disease-specific survival of HCC patients. GSEA suggested that DDOST is closely correlated with cell cycle and immune response via the PPAR signaling pathway. ssGSEA indicated that DDOST expression was positively correlated with the infiltrating levels of Th2 cells and negatively correlated with the infiltration levels of cytotoxic cells. Conclusion: All those findings indicated that DDOST was correlated with prognosis and immune infiltration in HCC.